Efficacy evaluation of acupuncture combined with Liujunzi Decoction in the treatment of functional dyspepsia: A protocol of randomized controlled trial - Zhang, Yulan; Bian, Lihong; Long, Huan; Zhang, Weichen; Hu, Yuqiong (Medicine (Baltimore), 2021)
Functional dyspepsia (FD) is a common and frequently-occurring disease in internal medicine. It is known that Liujunzi decoction and acupuncture are widely used in the treatment of FD, but there are few studies on the combination of Liujunzi decoction and acupuncture in the treatment of FD, and its safety and efficacy are still controversial. Therefore, the purpose of this study is to evaluate the efficacy and safety of acupuncture combined with Liujunzi decoction in the treatment of FD. We designed a prospective randomized controlled trial. The study protocol was approved by the Clinical Research Ethics Committee of our hospital. Patients with FD were randomly assigned to the treatment group of acupuncture combined with Liujunzi Decoction (the experimental group) and the treatment group of Liujunzi Decoction (the control group) in a ratio of 1:1. Outcome indicators were Nepean Dyspepsia Index, the MOS item short from health survey, and adverse reactions. Finally, SPSS 18.0 software would be used for statistical analysis of the data. This study will evaluate the efficacy and safety of acupuncture combined with Liujunzi Decoction in the treatment of FD and provide clinical basis for the use of acupuncture combined with Liujunzi Decoction in the treatment of FD. DOI 10.17605/OSF.IO/67GKN.